Non-Linear Correlation Between Tumor Size and Survival Outcomes for Parathyroid Carcinoma: A SEER Population-Based Cohort Study - Zhang, Kun; Su, Anping; Wang, Xiaofei; Zhao, Wanjun; He, Linye; Wei, Tao; Li, Zhihui; Zhu, Jingqiang; Chen, Ya-Wen (Frontiers in Endocrinology, 2022)
Background: Parathyroid carcinoma (PC) is a rare malignancy without a commonly acknowledged prognostic assessment and treatment system. This study captures how independent prognostic factors and tumor size correlate with outcomes in patients with PC. Methods: The Surveillance, Epidemiology, and End Results database was used to perform a retrospective analysis on PC patients from 2000 to 2018. Univariate and multivariable survival analyses were performed to evaluate cancer-specific survival (CSS) and overall survival (OS), to identify independent prognostic factors in the PC patient population. A generalized additive model was applied to conduct smooth curve fitting and to examine the association between tumor size and relative risk of death. Results: A total of 590 patients were included. The 5- and 10-year OS were 80.8% and 67.1%, respectively. 5- and 10-year CSS was estimated to be 93.6% and 92.1%, respectively. The association between tumor size and relative risk of death can be generalized as a U-shaped curve. The mortality risk reaches its lowest point when tumor diameter approaches 2cm. At a tumor diameter cutoff of 3cm for CSS and 4cm for OS, there is an abrupt drop in survival rates. Multivariate Cox analysis revealed age, no surgery, and debulking surgery as consistent predictors of lower OS and CSS. Conclusions: A non-linear correlation between tumor size and death risk has been identified in patients with PC, along with an accurate size threshold at which survival rates sharply decrease. Further investigation is needed to determine if these trends are seen in other malignancies with promising prognoses.